Crop rotation in Guarapuava. XIV. Effects of winter crops succession systems on some agronomic characteristics of corn under no tillage - dos Santos, Henrique Pereira; Pereira, Luiz Ricardo (Pesquisa Agropecuaria Brasileira, 1994)
During six years the effects of common vetch (Vicia sativa L.), and lupins (Lupinus sp.) on corn (Zea mays) were evaluated at the Cooperativa Agrária Mista Entre Rios Ltda., Guarapuava, PR, Brazil. Corn was established under no-tillage system in a complete randomized block design with four replications. Corn was hand-harvested in plots of 60 m2. In corn cultivated after a) common vetch and wheat or b) after common vetch, wheat and flax grain, yield and number of kernels per plant were higher than under c) after lupins, wheat, oats, and barley. Increments in number of kernels per plant resulted in higher corn yield observed under rotation system. Common vetch showed to be the species with the greatest potential for use as an alternative crop for wheat or corn in rotation systems.